KARELIAN CARBONATE SEDIMENTATION INVERSION ON THE BALTIC SHIELD. A REFLECTION OF GLOBAL CHANGES IN THE CONDITIONS OF PRECAMBRIAN EXOGENESIS? - Melezhik V.A.; Predovskiy A.A. (My University, 1989)
The tracing of the geochemical evolution of carbonate deposits in the earth's history is a major scientific problem. Our understanding of this evolution is in inverse relation to the age of sedimentary sequences. However, one cannot identify the main trends and cause-and-effect relationships in the evolution of the complex atmosphere-hydrosphere-lithosphere-biosphere system without deciphering the principal patterns of evolution of the carbonate sedimentation system over the entire length of earth history, and particularly in its key Precambrian stage. The authors emphasize that the inversion in carbonate accumulation that is identifiable in the Karelian stage on the Baltic Shield may well not be the only one in the Precambrian sequence of the region, but rather an expression of one of many revolutionary stages in a complex, prolonged sequence of geological events. In addition, each cycle of carbonate sedimentation within the two fundamentally different sedimentation systems of the Jatulian and Ludicovian exhibits regular fluctuations in the MgO:CaO ratio, induced by second-order or higher-order factors which nonetheless take place within the rigid framework of the global events.
Keywords: Precambrian; Precambrian; Докембрий